To Ally or Not? The Critical Factors of a New Alliance Model in Urban Infrastructure Projects - Valkama, Pekka; Oulasvirta, Lasse; Karppi, Ilari (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
The research explains the background of an alliance model which is a new collaborative project concept in urban infrastructure investments and reviews stakeholder views of applied alliances based on a case study analysing project experiences in the city of Tampere, Finland. The alliance model is considered a potential solution for some of the chronic productivity and other problems of the building industry and the classic difficulties in public-sector investment projects, but the model fits a purpose primarily only in publicly funded, technically challenging and sufficiently large projects. The alliance model has initiation, development and implementation phases, and of these phases, the interviewed experts named the development phases as particularly critical, as team spirit, shared ethos, and joint goals must all be built in that phase before the actual collaboration between contract parties can be initiated.